Disposal options for solid waste of Bangalore city based on its characteristics. (1st January 2013) - Naveen, B.P.; Sivapullaiah, P.V.; Sitharam, T.G.
A detailed analysis of Bangalore's solid waste has been done to suggest various management options for safe disposal. It has been observed that Bangalore's solid waste contains a larger proportion of degradable waste compared to many other cities. Based on detailed analysis of available data, it has been suggested that a landfill with a leachate and gas collection system is better than an inert landfill for Bangalore. Further, separation of degradable waste with an inert landfi ll is another option, but at the moment, the former option is preferred, for technical and economical reasons.